Lucifensin, a novel insect defensin of medicinal maggots: synthesis and structural study - Ceřovský, Václav; Slaninová, Jiřina; Fučík, Vladimír; Monincová, Lenka; Bednárová, Lucie; Maloň, Petr; Stokrová, Jitka (Chembiochem, 2011)
Recently, we identified a new insect defensin, named lucifensin that is secreted/excreted by the blowfly Lucilia sericata larvae into a wound as a disinfectant during the medicinal process known as maggot therapy. Here, we report the total chemical synthesis of this peptide of 40 amino acid residues and three intramolecular disulfide bridges by using three different protocols. Oxidative folding of linear peptide yielded a peptide with a pattern of disulfide bridges identical to that of native lucifensin. The synthetic lucifensin was active against Gram-positive bacteria and was not hemolytic. We synthesized three lucifensin analogues that are cyclized through one native disulfide bridge in different positions and having the remaining four cysteines substituted by alanine. Only the analogue cyclized through a Cys16-Cys36 disulfide bridge showed weak antimicrobial activity. Truncating lucifensin at the N-terminal by ten amino acid residues resulted in a drop in antimicrobial activity. Linear lucifensin having all six cysteine residues alkylated was inactive. Circular dichroism spectra measured in the presence of α-helix-promoting compounds showed different patterns for lucifensin and its analogues. Transmission electron microscopy revealed that Bacillus subtilis treatment with lucifensin induced significant changes in its envelope.
Keywords: larva; Animals; antiinfekční látky; Chromatography, High Pressure Liquid; Protein Folding; sbalování proteinů; disulfidy; Disulfides; Circular Dichroism; defensiny; sekundární struktura proteinů; Protein Structure, Secondary; zvířata; Defensins; Larva; vysokoúčinná kapalinová chromatografie; cirkulární dichroismus; Anti-Infective Agents